Exploring the Effects of Strategic Competence on ESP Students’ Academic Writing Process: Case of Third Year Students of Economics Department, M’sila University - Manal DJAIDJA; Khadidja Meryem OUALI (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2024)
In an ESP context, students struggle to write in English language, which is considered as the most important skill among the four language skills that students need in communicating through their thoughts and ideas. This study attempted to identify the challenges that face ESP third year students of Economics department of M'sila university in their writing. In addition to explore the effect of strategic competence on their academic writing process, as well as highlighting the types of strategies used by ESP students in a writing assignment; that are metacognitive, cognitive, and social affective strategies. In other words, this study aims at finding out whether the use of strategic competence helps ESP learners to improve their writing skills. To achieve this aim, the researchers used in this study the triangulation method; including students' questionnaire, teachers’ interview, and classroom observation. The questionnaire was submitted to the students of Economics department in order to gather as much effective answers as possible. The second instrument used was a structured interview with five English teachers in the same department, which contains of eleven questions. The third research tool was classroom observation that was conducted in five sessions regularly. The results show that third year students of Economics at M’sila University have difficulties in the process of writing and they are not aware of using strategic competence in their writing.
Keywords: Strategic Competence; Academic Writing Process; and Teaching English for Specific Purposes